The Influence of Cognitive and Emotional Biases on Investment Decisions through Financial Literacy - Raden Dian Hardiana; Nugraha Nugraha; Toni Heryana; Imas Purnamasari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Rapid growth of retail investor participation via digital platforms, investment quality remains inadequate, as numerous individuals continue to exhibit suboptimal decision-making driven by psychological influences. This study investigates the impact of cognitive and emotional biases on investment decisions, utilizing financial literacy as a mediating variable among retail investors in West Java and Banten, Indonesia. Employing a quantitative research design with a survey method, data gathered from experienced retail investors were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The empirical findings indicate that cognitive and emotional biases exert a significant negative effect on financial literacy, whereas financial literacy demonstrates a significant positive influence on investment decisions. Furthermore, financial literacy significantly mediates the relationship between both categories of psychological biases and investment decisions. The proposed model exhibits moderate explanatory and predictive power, thereby confirming its adequacy in explaining investor behavior. Consequently, these findings imply that financial literacy plays a pivotal role in mitigating the adverse effects of psychological biases in investment decision-making. The study concludes that enhancing financial literacy is imperative to foster rational investment behavior, suggesting that financial education initiatives must integrate strategic interventions to diminish cognitive and emotional distortions.